Electrocoagulation of food waste digestate and the suitability of recovered solids for application to agricultural land. (August 2021) - Reilly, Matthew; Cooley, Andrew P.; Richardson, Brittany; Tito, Duarte; Theodorou, Michael K.
Highlights: Electrocoagulation was performed on anaerobic digestates from food waste. Electrocoagulated solids were found to be suitable for land spreading. Over 90 % of soluble phosphorous was recovered by electrocoagulation of digestate. Electrocoagulation did not influence the concentration of ammonium in digestate. Abstract: Digestates from anaerobic digestion (AD) of food waste contain fertiliser nutrients (such as P and N) which are valuable for agricultural purposes and can be environmentally hazardous if disposal is uncontrolled. Here, we applied electrocoagulation (EC) for treatment of digestates, to separate liquids and nutrient-rich solids. Coagulant-dosing electrocoagulation (CDEC) was used to compare Al and steel anodes for treatment of digestate from AD fermenters fed a controlled diet representative of food waste. When applying metal dosing concentrations of 0–4.66 mM, Fe was found to be up to 29.8 % superior to Al in terms of aiding removal of chemical oxygen demand (COD). To mitigate plate fouling, the digestate was diluted to 0.25 and 0.1 concentrations to enable successful treatment by continuous-flow electrocoagulation (CFEC). The highest recovery of soluble P per Fe added by CFEC was 22.4 mg-P g-Fe −1 . This was achieved when using 2.33 mM Fe to treat a 0.25 dilution of digestate. In comparison to a control, these optimal conditions also caused a reduction of 4.5 mg L −1 (or 87.7 %) of soluble P and the removal of 254 mg L −1 (33.2 %) of COD in the filtrate. The NH4 + concentration in filtrate was not influenced by EC treatment. Analyses of a range of known toxic elements (Cu, Ni, Zn, As, Cd, Cr, Mo and Pb) indicates that the solids recovered by CFEC could be suitable for application to land.